Robustness of Exponential Dissipation with respect to Small Time Delay - Xunwu Yin (Abstract and Applied Analysis)
We investigate robustness of exponential dissipation for the following general nonlinear evolutionary equation with small time delay: We firstly obtain a converse Lyapunov theorem. With the help of it, we establish an important result on robustness of exponential dissipation to small time delay assuming that the nonlinearity is globally Lipschitz.